EXÁMEN ESPECIAL AL RUBRO ACTIVO CORRIENTE A LA “COOPERATIVA DE TRANSPORTE CENTRAL CATAMAYO”, PERIODO 2021 - Nagua Rivas., Kevin Monfilio (2024)
The Curricular Integration Work named Special Examination of the Current Assets Section at “Cooperativa de Transporte Central Catamayo”, for the period of 2021, was conducted with the purpose of evaluating the internal control, determining the reasonableness of the balances of the accounts examined, culminating in the delivery of an audit report. This report includes comments, conclusions, and recommendations that will allow for improvement actions. The special examination began with a preliminary visit to the company, based on a guide, which allowed for the identification of deficient areas and the establishment of an audit program and an internal control questionnaire. The second phase was the Execution, where the activities described in the audit program were carried out, including the application of the internal control questionnaire and its corresponding evaluation, and the preparation of a Report, in which concrete actions were established for the implementation of the necessary changes. In summary, the work allowed the identification of internal control weaknesses and the determination of the reasonableness of the current assets balances of the company, proposing corrections to the following identified findings: lack of development of corrective measures for shortages or overages in cash counts. Thus, it was found that one branch had a cash shortage; as well as a lack of a procedures manual for the management and control of accounts and documents receivable and inventories; the cooperative's inventories lack insurance against theft, fire, or natural disasters: lack of guarantee from the personnel guarding the inventory; the entity does not have an adequate separation of responsibilities in its processes: given the weaknesses pointed out, recommendations were proposed that will contribute to making changes in the Internal Control in order to make corrective decisions and promote its efficiency and administrative solidity.